The Turing Test and the Issue of Trust in AI Systems - Stacewicz Paweł; Sołoducha Krzysztof (Studies in Logic, Grammar and Rhetoric)
The Turing test, which is a verbal test of the indistinguishability of machine and human intelligence, is a historically important idea that has set a way of thinking about the AI (artificial intelligence) project that is still relevant today. According to it, the benchmark/blueprint for AI is human intelligence, and the key skill of AI should be its communicative proficiency – which includes explaining decisions made by the machine.